Affinity separation and subsequent terminal differentiation of acute myeloid leukemia cells using the human transferrin receptor (CD71) as a capture target. Issue 10 (15th April 2019) - Lyons, Veronica J.; Pappas, Dimitri
Abstract : The microfluidic detection of myeloblasts in blood via the human transferrin receptor (CD71) can serve as a diagnostic marker for acute myeloid leukemia (AML). Abstract : The microfluidic detection of myeloblasts in blood via the human transferrin receptor (CD71) can serve as a diagnostic marker for acute myeloid leukemia (AML). Furthermore, CD71 expression is present in all proliferating cells and can capture target cells without prior knowledge of AML subtype. The use of anti-CD71 as the affinity ligand for AML detection in this work yields a capture efficiency and purity during peak CD71 expression of 92% and 62%, respectively. Additionally, target cells were isolated from lysed, preserved blood samples with a capture purity of 32% at a concentration of 10% myeloblasts in blood, half of the current diagnosis threshold determined by the World Health Organization. Cells isolated using this capture ligand were then subjected to post-separation differentiation therapy. HL60 cells were differentiated into non-proliferating, neutrophil-like cells. After 48 hours of incubation with 1.5% DMSO, there was a decrease in the CD71 antigen expression in differentiated cells. This separation approach can be used to screen blood samples for AML cells, and the effluent of the separation is available for post-separation analyses.